Nanogranular magnetic film and electronic component
The nanogranular magnetic film, with its unique structure and atomic ratio, addresses the challenge of achieving high saturation magnetic flux density and specific resistance, making it ideal for high-frequency electronic components.
Patent Information
- Application Number
- JP2024124916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-10
Smart Images

Figure 2025060412000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a nanogranular magnetic film and an electronic component. [Background technology]
[0002] In recent years, mobile devices such as smartphones and smart watches are simultaneously required to have larger display screens, increased battery capacity, smaller size, and lighter weight. The demands for larger display screens and increased battery capacity are contradictory to the demands for smaller size and lighter weight. In order to meet these contradictory demands, there is a demand for smaller circuit boards. There is a demand for smaller power supply circuits, which occupy a particularly large area of the circuit board. Furthermore, there is a demand for smaller inductors, which occupy a particularly large mounting area of the power supply circuit.
[0003] In order to reduce the size of an inductor, it is particularly effective to increase the drive frequency of the power supply circuit, which requires a switching element that can be driven at a high frequency.
[0004] Traditionally, switching elements for power supply circuits were made of silicon, which limited the operating frequency of the power supply circuit. This was due to the limitations of the physical properties of silicon. However, in recent years, semiconductors with superior physical properties to silicon, such as GaN and SiC, are beginning to be used for switching elements.
[0005] By using semiconductors with good high-frequency characteristics such as GaN for switching elements, it becomes possible to drive the switching elements at high frequencies, and to achieve high-frequency drive of power supply circuits. For example, switching elements made of GaN are capable of switching at much higher frequencies than conventional silicon switching elements, and can drive power supply circuits at much higher frequencies.
[0006] By driving power supply circuits at high frequencies, passive components, especially large power supply inductors, can be significantly miniaturized. This allows the power supply circuit to be significantly miniaturized. To enable high-frequency driving of power supply inductors, it is necessary to realize a magnetic material with high magnetic permeability in the high-frequency range and use it as the inductor's magnetic core material.
[0007] Thin film inductors are the most suitable form of small inductor for power supplies that can handle high frequency drive. Thin film inductors are manufactured by stacking coils, terminals, magnetic films, insulating layers, etc. on a substrate using semiconductor processes. In thin film inductors, the magnetic film serves as the magnetic core, so the characteristics of the thin film inductor depend heavily on the characteristics of the magnetic film.
[0008] Patent Document 1 describes an amorphous alloy having a structure in which fine particles containing a metal element are dispersed in an amorphous film made of a nitrogen compound. This type of structure is now sometimes called a nanogranular structure. And a magnetic film having this structure is sometimes called a nanogranular magnetic film.
[0009] Nanogranular magnetic films have a higher saturation magnetic flux density Bs than ferrite materials and a higher resistivity ρ than general magnetic alloys, and therefore have high magnetic permeability at high frequencies. Therefore, the application of nanogranular magnetic films to thin film inductors is being considered.
[0010] Furthermore, Patent Document 2 describes a nanogranular magnetic film that contains elements such as Fe and Co and has various parameters measurable by a three-dimensional atom probe within specific ranges. The nanogranular magnetic film has a high coercive force and a low saturation magnetic flux density. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 60-152651 [Patent Document 2] International Publication No. 2023 / 127199 Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a nano-granular magnetic film having a high saturation magnetic flux density Bs and a high resistivity. [Means for solving the problem]
[0013] In order to achieve the above object, the nanogranular magnetic film according to the present invention comprises: A nanogranular magnetic film having a structure in which minute domains of a first phase are dispersed in a second phase, The first phase contains Fe and Co, and the second phase contains one or more selected from O, N and F, A measurement range is set in the nanogranular magnetic film, the measurement range is divided into 80,000 or more 1 nm x 1 nm x 1 nm grids, and Fe / (Fe+Co) and the second phase compound of each grid are measured by atomic ratio, and each grid is divided into an MX-rich grid in which the concentration of the second phase compound is above the average, and an MX-poor grid in which the concentration of the second phase compound is below the average, The CV value of Fe / (Fe+Co) calculated for each MX-rich grid is larger than the CV value of Fe / (Fe+Co) calculated for each MX-poor grid.
[0014] The volume ratio of the first phase to the total volume of the first phase and the second phase may be 40% or more and 65% or less.
[0015] The average value of Fe / (Fe+Co) calculated for each grid may be equal to or greater than 0.15 and equal to or less than 0.85.
[0016] The electronic component according to the present invention has the above-mentioned nanogranular magnetic film. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a schematic cross-sectional view of a nanogranular magnetic film. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of a production apparatus. [Diagram 3] FIG. [Figure 4] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0019] As shown in FIG. 1, the nano-granular magnetic film 1 according to this embodiment has a structure in which minute domains of a first phase 11 are dispersed in a second phase 12, that is, a nano-granular structure.
[0020] The nanogranular magnetic film refers to a thin film having the above structure, in which the second phase is not a resin. A ribbon or a compact is not literally a nanogranular magnetic film even if it has a structure in which minute domains of the first phase 11 are dispersed in the second phase 12.
[0021] The average size of the microdomains of the first phase 11 is nanometer size, that is, 30 nm or less. The average size of the microdomains of the first phase 11 may be 15 nm or less. There is no particular limitation on the method for measuring the size of the microdomains of the first phase 11. For example, the circle-equivalent diameter of the microdomains of the first phase 11 in the cross section of the nano-granular magnetic film 1 may be taken as the size of the microdomains of the first phase 11.
[0022] The circle-equivalent diameter of the micro domain of the first phase 11 in the cross section of the nano-granular magnetic film 1 refers to the diameter of a circle having an area equal to the area of the micro domain of the first phase 11 in the cross section of the nano-granular magnetic film 1.
[0023] The first phase 11 is a phase containing a metal element. Specifically, it contains Fe and Co. There is no particular limitation on how Fe and Co are contained in the first phase 11. For example, Fe and Co may be contained in the first phase 11 in any ratio, Fe and Co may be contained in the first phase 11 as an alloy with other metal elements, or Fe and Co may be contained in the first phase 11 as a compound with other elements. The compound contained in the first phase 11 may be a magnetic oxide material. For example, it may be ferrite.
[0024] There is no particular restriction on the total content of Fe and Co in the first phase 11. The ratio of the total content of Fe and Co to the total content of Fe, Co, X1 and X2 in the first phase 11 may be 75 at% or more, 80 at% or more, 90 at% or more, or 95 at% or more. However, in calculating this ratio, elements whose content in the second phase 12 is higher than that in the first phase 11 are not included in X1 and X2.
[0025] X1 is a metalloid element, for example, one or more metalloid elements selected from B, Si, P, C, and Ge.
[0026] X2 is a metal element other than Fe and Co. For example, it may be one or more metal elements selected from Nb, Mo, Cu, Ti, Zr, Cr, Mn, V, W, Al, and Ni.
[0027] The first phase 11 may contain elements other than Fe, Co, X1, and X2. The ratio of the total content of elements other than Fe, Co, X1, and X2 to the total content of Fe, Co, X1, and X2 may be 10 at% or less, or 5 at% or less.
[0028] The second phase 12 is a phase containing a nonmetallic element. Specifically, the second phase 12 is a phase containing one or more elements selected from O, N, and F. There is no particular limitation on how the one or more elements selected from O, N, and F are contained in the second phase 12. For example, the one or more elements selected from O, N, and F may be contained in the second phase 12 as a compound with other elements. That is, the second phase 12 may contain an oxide, nitride, oxynitride, and / or fluoride of some element other than O, N, and F. The second phase 12 may contain an oxide, nitride, and / or fluoride of some element other than O, N, and F. The second phase 12 may also be a mixed phase of oxides, nitrides, and / or fluorides.
[0029] When the compound contained in the second phase 12 is an oxynitride, the ratio of the nitrogen content to the total content of oxygen and nitrogen in the second phase 12 (hereinafter, may be referred to as N / (N+O)) may be greater than 0 at% and less than 46 at%, or may be 15 at% or more and 46 at% or less. There is no particular limitation on the method of measuring N / (N+O) in the second phase 12. For example, it may be measured using an impulse heating melting extraction method. However, it is difficult to use XRF. This is because it is difficult to measure the content of elements with small atomic numbers such as O and N, and it is difficult to ensure accuracy.
[0030] There is no particular limit to the type of the second phase compound. For example, SiO2, Al2O3, AlN, Si3N4, MgF2, BN, MgO, GaO2, GeO2, Si3N4·Al2O3, etc. may be mentioned. In addition, the oxides among the above compounds may be oxynitrides in which oxygen is partially replaced with nitrogen. That is, the compound contained in the second phase 12 may be an oxynitride of Si, an oxynitride of Al, an oxynitride of Mg, an oxynitride of Ga, or an oxynitride of Ge, or may be an oxynitride of Si, an oxynitride of Al, an oxynitride of Mg, or an oxynitride of Ga.
[0031] The nanogranular magnetic film according to this embodiment is (Fe x Co y X1a X2 b )-X3, X1 is one or more selected from the group consisting of B, P, C and Ge; X2 is one or more selected from the group consisting of Nb, Mo, Cu, Al, Ti, Zr, Cr, Mn, V, W, Al, and Ni; X3 is one or more selected from the group consisting of SiO2, Al2O3, AlN, Si3N4, MgF2, BN, MgO, GaO2, GeO2, Si3N4·Al2O3, oxynitride of Si, oxynitride of Al, oxynitride of Mg, oxynitride of Ga, and oxynitride of Ge; 0.15≦x≦0.85 0.15≦y≦0.85 0≦a≦5.0 0≦b≦10.0 0.90≦x+y+a+b≦1.00 may be satisfied.
[0032] The above formula indicates that the composition of the first phase 11 is Fe x Co y X1 a X2 b and indicates that the second phase 12 is composed of X3. X3 may be one or more selected from the group consisting of SiO2, Al2O3, AlN, Si3N4, MgF2, BN, MgO, GaO2, GeO2, Si3N4·Al2O3, and oxynitrides of Si (referred to as Si-ON). The volume ratio of the first phase 11 to the second phase 12 will be described later.
[0033] The nano-granular magnetic film 1 according to this embodiment may contain, as an impurity, an element that is not contained in either the elements constituting the first phase 11 or the elements constituting the second phase 12. The nano-granular magnetic film may contain 5 at % or less of impurities, assuming that the total ratio of the elements contained in the nano-granular magnetic film is 100 at %.
[0034] The volume ratio of the first phase 12 to the total volume of the first phase 11 and the second phase 12 is not particularly limited. For example, it may be 70% or less, or 65% or less. That is, when the volume ratio of the first phase 11 is V1 and the volume ratio of the second phase 12 is V2, V1 / (V1+V2) may be 0.70 or less (70% or less), or V1 / (V1+V2) may be 0.65 or less (65% or less). V1 / (V1+V2) may be 0.60 or less (60% or less). As the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12 increases, Bs increases but the resistivity decreases.
[0035] There is no particular lower limit to the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12. It may be 30% or more, or 35% or more. That is, V1 / (V1+V2) may be 0.30 or more (30% or more). It may be 0.35 or more (35% or more). V1 / (V1+V2) may be 0.40 or more (40% or more). As the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12 decreases, the resistivity increases but Bs decreases.
[0036] The first phase 11 may have a crystal structure. Specifically, the first phase 11 may have a bcc crystal structure. By having the bcc crystal structure, the saturation magnetic flux density Bs tends to be high. The average crystal grain size of the crystals contained in the crystal structure of the first phase may be 1 nm or more and 30 nm or less, and more preferably 1.5 nm or more and 15 nm or less.
[0037] There is no particular limitation on the method for confirming the above crystal structure and the average crystal grain size of the crystals. For example, the crystal structure can be confirmed by analyzing the X-ray diffraction pattern by XRD, or the electron diffraction pattern by TEM or the like. The average crystal grain size can also be confirmed by TEM images, STEM images, or the like. The average size of the micro-domains of the first phase 11 can be regarded as the average crystal grain size of the crystals.
[0038] There is no particular limitation on the method of measuring the volume ratio V1 / (V1+V2) of the first phase 11 to the total volume of the first phase 11 and the second phase 12. For example, it can be calculated from the results of XRF measurement of the nanogranular magnetic film 1. Alternatively, it may be calculated from the area of the first phase 11 to the total area of the first phase 11 and the second phase 12 by observing the cross section of the nanogranular magnetic film 1 with a TEM. In this case, the area ratio is converted to a volume ratio.
[0039] The nanogranular magnetic film 1 may contain only the first phase 11 and the second phase 12, but may also contain a heterogeneous phase other than the first phase 11 and the second phase 12. There is no particular restriction on the proportion of the heterogeneous phase, but the area ratio of the heterogeneous phase may be 10% or less when the cross section of the nanogranular magnetic film 1 is observed by TEM. In addition, a part or the whole of the heterogeneous phase may be voids.
[0040] In FIG. 1, all of the first phases 11 are separated from each other, but some of the first phases 11 may be in contact with each other.
[0041] The thickness of the nano-granular magnetic film 1 is arbitrary. For example, it may be 50 nm or more and 200,000 nm or less. Also, a suitable thickness may be selected depending on the application. There is no particular limit to the method for measuring the thickness of the nano-granular magnetic film 1. For example, it can be measured using a TEM, SEM, a step thickness gauge, or the like. Also, the reliability of the measurement results obtained may be confirmed by correlating in advance between multiple measuring devices.
[0042] Nanogranular magnetic film 1 with a volume of 80,000 nm 3 The above measurement range is set, and the measurement range is divided into 80,000 or more 1 nm x 1 nm x 1 nm cubic grids, and the atomic ratio of the constituent elements is measured for all grids. Then, Fe / (Fe+Co) of each grid and the concentration of the second phase compound of each grid are measured in terms of the atomic ratio of the constituent elements.
[0043] Grids whose concentrations of second-phase compounds are equal to or greater than the average concentration of second-phase compounds are classified as MX-rich grids, and those whose concentrations of second-phase compounds are less than the average concentration of second-phase compounds are classified as MX-poor grids. The average concentration of second-phase compounds is calculated by averaging the concentrations of second-phase compounds in all grids. MX-rich grids are grids that contain a relatively large amount of second-phase compounds, i.e., grids that contain a relatively large amount of second phase. In contrast, MX-poor grids are grids that contain a relatively large amount of first phase.
[0044] The average concentration of the second phase compound in all the grids is approximately equal to the content ratio of the second phase compound to the total content of Fe, Co and the second phase compound in the nanogranular magnetic film 1.
[0045] A nanogranular magnetic film in which the CV value calculated from the Fe / (Fe+Co) value of an MX-rich grid is larger than the CV value calculated from the Fe / (Fe+Co) value of an MX-poor grid has a higher resistivity to Bs than a conventional nanogranular magnetic film having the same composition and structure except for the above. In other words, it is a superior material as a core material for a thin film inductor. The CV value is a parameter calculated by dividing the standard deviation by the average value.
[0046] The above parameters can be measured using a three-dimensional atom probe (3DAP).
[0047] The average value of Fe / (Fe+Co) calculated for each grid may be 0.15 or more and 0.85 or less. The average value of Fe / (Fe+Co) calculated for each grid generally coincides with the average value of Fe / (Fe+Co) in the entire nanogranular magnetic film.
[0048] A method for manufacturing the nanogranular magnetic film according to this embodiment will be described below.
[0049] The nanogranular magnetic film according to this embodiment is manufactured by a sputtering method using the manufacturing apparatus shown in Figures 2 to 4, for example. Figure 2 is a schematic diagram showing a cross section of the manufacturing apparatus. Figure 3 is a schematic diagram of the manufacturing apparatus (particularly the rotating plate 111a and the substrate 113) observed along the arrow direction of line III-III in Figure 2. Figure 4 is a schematic diagram of the manufacturing apparatus (particularly the shutter 131 and the sputtering target 123) observed along the arrow direction of line IV-IV in Figure 2.
[0050] A substrate 113 on which a nano-granular magnetic film is to be sputtered is fixed to a rotating plate 111a of a rotating member 111. In addition, the rotating plate 111a is fixed to a rotating shaft 111b.
[0051] Any type of substrate may be used as the substrate 113 on which the nanogranular magnetic film is sputtered. For example, a silicon substrate, a silicon substrate with a thermally oxidized film, an MgO substrate, a (non-magnetic) ferrite substrate, a sapphire substrate, a glass substrate, a glass epoxy substrate, etc. However, the type of substrate is not limited to these, and various ceramic substrates and various semiconductor substrates can be used.
[0052] On the various substrates described above, members (e.g., coils, wiring) constituting a product or a part (e.g., a thin film inductor) may be fabricated. For example, a coil pattern, wiring pattern, etc. for a thin film inductor may be fabricated on a substrate for a thin film inductor.
[0053] Moreover, a foil or sheet of metal, plastic, resin, or the like can be used as the substrate 113 in place of the various substrates mentioned above.
[0054] As pretreatment of the substrate 113, it is preferable to perform a surface treatment under normal pressure using the UV / O3 method, and a surface treatment in a vacuum such as reverse sputtering, ion milling, or plasma cleaning. Since the magnetic film for a thin-film inductor is thick, the problem of film peeling due to stress is significant. However, by performing both of the above surface treatments, the problem of film peeling is greatly improved. There is no particular limit to the treatment time for each surface treatment. For example, the treatment time for the UV / O3 method may be 0.5 minutes or more and 60 minutes or less. Furthermore, when reverse sputtering is performed as the surface treatment in a vacuum, the treatment time for the reverse sputtering may be 0.1 minutes or more and 20 minutes or less.
[0055] There are no particular limitations on the shapes of rotating plate 111a and shutter 131 shown in Figures 3 and 4. For example, the outer periphery may be a perfect circle. The intersection point of dotted line C in Figure 2 and the surface of rotating plate 111a including substrate 113 is defined as point C', and the intersection point of dotted line C in Figure 2 and shutter 113 is defined as point C''. Point C' is the center of rotating plate 111a whose outer periphery is a perfect circle, and point C'' is the center of shutter 113 whose outer periphery is a perfect circle.
[0056] The sputtering target 123 is mounted in the sputtering device 121. The type of the sputtering target 123 is arbitrary. However, in order to easily obtain a nanogranular magnetic film in which the CV value calculated from the Fe / (Fe+Co) value of the above-mentioned MX-rich grid is larger than the CV value calculated from the Fe / (Fe+Co) value of the MX-poor grid, it is preferable to use, as the sputtering target 123, a sputtering target produced by mixing and sintering Fe and Co, or an FeCo alloy and a compound mainly contained in the second phase.
[0057] Furthermore, chips of simple substances or compounds of elements other than Fe, Co, and compounds mainly contained in the second phase may be appropriately placed on the surface of the sputtering target 123. By placing the chips, simple substances or compounds of elements other than Fe, Co, and compounds mainly contained in the second phase can be contained in the nanogranular magnetic film. When simple substances or compounds of elements other than Fe, Co, and compounds mainly contained in the second phase are contained in the nanogranular magnetic film by the above method, the simple substances or compounds of elements other than Fe, Co, and compounds mainly contained in the second phase may be contained in either the first phase or the second phase.
[0058] However, when a target prepared by a sintering method or melting method on which Fe chips, Co chips, and / or chips of a compound mainly contained in the second phase are arranged is used as the sputtering target 123 instead of using the above-mentioned mixed sintered sputtering target, the CV value of Fe / (Fe+Co) calculated for each MX-rich grid is unlikely to be larger than the CV value of Fe / (Fe+Co) calculated for each MX-poor grid, and the resistivity to Bs decreases. Examples of targets prepared by the above-mentioned sintering method or melting method include targets made of only FeCo alloys and targets made of only compounds mainly contained in the second phase.
[0059] There is no particular limitation on the type of sputtering device 121, as long as it can form a nano-granular magnetic film on the substrate 113 by sputtering.
[0060] As shown in FIG. 4, the shutter 131 has a hole above the sputter target 123 .
[0061] Then, sputtering is performed while rotating the rotating plate 111a by rotating the rotating shaft 111b, whereby a nano-granular magnetic film is intermittently formed on the substrate 113.
[0062] By appropriately adjusting the number of rotations of the rotating plate 111a and the lengths of L1 to L5, the time for continuous deposition of the nano-granular magnetic film and the thickness of the continuous deposition film are changed. Then, a multi-layer film of the nano-granular magnetic film is formed in a pseudo manner. That is, a multi-layer film of the nano-granular magnetic film is formed in a pseudo manner by repeating the deposition process and the relaxation process.
[0063] In reality, it is not possible to confirm where the boundaries between the films are even using a TEM, so the word "pseudo" is used. However, by forming a multilayer film of the nanogranular magnetic film pseudo-wise, a nanogranular magnetic film is formed in which the CV value of Fe / (Fe+Co) calculated for the MX-rich grid is greater than the CV value of Fe / (Fe+Co) calculated for the MX-poor grid. The resistivity of the nanogranular magnetic film thus formed with respect to Bs increases. The reason for this is unclear, but it is thought to be due to the stress in the nanogranular magnetic film being relaxed by the intermittent formation of the nanogranular magnetic film.
[0064] There is no particular limit to the deposition time per layer (hereinafter, sometimes referred to as the continuous deposition time) and the deposition thickness per layer (hereinafter, sometimes referred to as the continuous deposition thickness) of the pseudo-formed multilayer film. The continuous deposition time may be 0.7 seconds or more and 5.0 seconds or less, particularly 3.4 seconds or less. The continuous deposition thickness may be 0.4 nm or more and 3.0 nm or less, particularly 2.0 nm or less. In particular, when the continuous deposition time and the continuous deposition thickness are increased by reducing the rotation speed, the CV value of Fe / (Fe+Co) calculated for each MX-rich grid is unlikely to be larger than the CV value of Fe / (Fe+Co) calculated for each MX-poor grid, and the resistivity against Bs tends to be smaller.
[0065] Although there is no particular restriction on the atmosphere during sputtering, it is preferable to use an inert gas (e.g., Ar gas, Kr gas, Xe gas, Ne gas) with 0.05% to 3%, particularly 0.2%, of O2 gas added. When sputtering is performed in an atmosphere with insufficient O2 gas added, the CV value of Fe / (Fe+Co) calculated for the MX-rich grid tends to be smaller than the CV value of Fe / (Fe+Co) calculated for the MX-poor grid, and the resistivity to Bs tends to be smaller.
[0066] The nanogranular magnetic film formed by sputtering may be subjected to an annealing treatment. The temperature of the annealing treatment is not particularly limited, but may be about 200° C. to 500° C., or may be 250° C. to 450° C. The time of the annealing treatment is not particularly limited, but may be about 0.1 minutes to 180 minutes.
[0067] The magnetic properties of the obtained nanogranular magnetic film can be measured by any method, for example, by using a VSM.
[0068] Although one embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. For example, in the above manufacturing method, the sputtering device is fixed and the substrate is rotated, but the sputtering device may be rotated and the substrate may be fixed. In addition, as long as the manufacturing method can form a multilayer film of a nanogranular magnetic film in a pseudo manner, a manufacturing method other than the method of rotating one of the substrate and the sputtering device may be used.
[0069] There is no particular limitation on the use of the nanogranular magnetic film according to this embodiment. The magnetic material including the nanogranular magnetic film is particularly suitable for use in electronic components that are used at high frequencies and require high Bs and resistivity. Examples of such applications include capacitors, thin film inductors, noise filters, separators, magneto-optical elements, TMR heads, GMR heads, magnetic sensors, and magnetic recording media. EXAMPLES
[0070] The present invention will be specifically described below with reference to examples.
[0071] (Experimental Example 1) A nanogranular magnetic film was formed on a substrate using the apparatus shown in Figures 2 to 4. L1 = 90 mm, L2 = 2 inches, L3 = 3 inches, L4 = 2 inches, and L5 = 4 inches. A silicon substrate with a thermal oxide film having a thickness of 0.28 mm was used as the substrate. In addition, as a pretreatment of the substrate, a surface treatment was performed by the UV / O3 method for 20 minutes. After that, reverse sputtering was performed for 5 minutes with an Ar gas pressure of 1 Pa and RF of 100 W.
[0072] A sputtering target having a thickness of 2 mm and a composition capable of obtaining a magnetic film having the composition shown in each table was prepared.
[0073] Then, a nanogranular magnetic film was formed by sputtering using the apparatus shown in Figures 2 to 4. Table 1 shows the presence or absence of pretreatment (UV / O3, reverse sputtering), the rotation speed of the rotating plate during sputtering, the continuous film formation time, the thickness of the continuous film formation, the presence or absence of O2 in the Ar gas, and whether the target was a mixed sintered target. The sputtering apparatus used was the SPF430H manufactured by Anelva Corporation.
[0074] It was confirmed by simple quantification using EDX (manufactured by JEOL Ltd.) that the compositions of the first phase and the second phase in the obtained nanogranular magnetic film were the compositions shown in Table 1.
[0075] It was confirmed by using XRF (Primus 4 manufactured by Rigaku Corporation) that the V1 / (V1+V2) values in the obtained nanogranular magnetic film were as shown in Table 1.
[0076] It was confirmed by using a TEM (JEM2100F manufactured by JEOL Ltd.) that the nanogranular magnetic film of each sample had a structure in which minute domains of the first phase were dispersed in the second phase.
[0077] The measurement method of each parameter using 3DAP will be described. First, in the obtained nanogranular magnetic film, a rectangular parallelepiped with a side length of 40 nm x 40 nm x 50 nm was set as the measurement range, and 80,000 grids of 1 nm x 1 nm x 1 nm were set in a continuous measurement range. Then, the Fe content, Co content, and content of second phase compound (SiO2 in Experimental Example 1) in each grid were measured by three-dimensional atom probe (3DAP). The content of each element was calculated by assuming that the total content of Fe, Co, Si, and O in each grid was 100 at%. Then, Fe / (Fe+Co) of each grid was calculated as the atomic ratio. Furthermore, the SiO2 content of each grid was calculated, and grids with SiO2 content above the average were designated as MX-rich grids, and grids with SiO2 content below the average were designated as MX-poor grids.
[0078] The standard deviation and average value of Fe / (Fe+Co) in the MX-rich grid were calculated, and the CV value of the MX-rich grid was calculated by dividing the standard deviation by the average value. Similarly, the standard deviation and average value of Fe / (Fe+Co) in the MX-poor grid were calculated, and the CV value of the MX-poor grid was calculated by dividing the standard deviation by the average value.
[0079] The saturation magnetic flux density Bs was measured using a VSM (TM-VSM331483-HGC) manufactured by Tamagawa Seisakusho Co., Ltd.
[0080] The actual resistivity was calculated from the sheet resistance measured using a resistivity meter (Loresta-EP MCP-T360 manufactured by Mitsubishi Chemical Corporation).
[0081] The method for measuring the standard resistivity for calculating the figure of merit is shown below.
[0082] First, the Fe:Co in the first phase was determined by conventional sputtering without rotation. The nanogranular magnetic films were fabricated under substantially the same conditions except for the difference between the two, that is, the Fe:Co atomic ratio in the first phase was approximately 85:15, 70:30, 45:55, and 15:85.
[0083] The specific manufacturing conditions were: rotation speed 0, continuous film formation time 25000 seconds, process gas during sputtering was a mixture of Ar gas and 0.2% O2 gas, and continuous film thickness was within the range of (5000±200) nm. Nanogranular magnetic films were fabricated that had the same composition except for the Fe:Co ratio in the first phase. In Experimental Example 1, nanogranular magnetic films of Comparative Examples 1 to 4 were fabricated.
[0084] Next, for the nano-granular magnetic films of Comparative Examples 1 to 4, the saturation magnetic flux density Bs and the actual resistivity were measured by the above-mentioned method.
[0085] Next, the points of Comparative Examples 2 to 4 were plotted on an xy plane with the x-axis being Bs (T) and the y-axis being resistivity (Ωcm). Then, the formula of the performance curve was derived by power approximation. The formula of the performance curve derived from Comparative Examples 2 to 4 is y=0.0044×x -11.25 It was.
[0086] The resistivity obtained by substituting the Bs value of each nanogranular magnetic film into the derived performance curve equation was used as the reference resistivity. The performance index was calculated by dividing the measured resistivity of each nanogranular magnetic film by the reference resistivity. A performance index of 1.20 or higher was considered to be good.
[0087] Comparative Example 5 was carried out under the same conditions as Example 3, except that Ar was used as the process gas during sputtering. Comparative Example 6 was carried out by arranging Fe chips and Co chips of 5 mm×5 mm size on a commercially available SiO2 target so that the composition of the first phase, the composition of the second phase, and V1 / (V1+V2) of the finally obtained nanogranular magnetic film were the same as those in Example 3.
[0088] Comparative Example 7 was carried out under the same conditions as in Example 3, except that the UV / O3 treatment and reverse sputtering were not carried out.
[0089] [Table 1]
[0090] From Table 1, in Examples 1 to 5 in which the rotating plate was rotated at a rotation speed of 12 rpm, the CV value of Fe / (Fe+Co) calculated for each MX-rich grid (hereinafter, sometimes referred to as MX-rich) was larger than the CV value of Fe / (Fe+Co) calculated for each MX-poor grid (hereinafter, sometimes referred to as MX-poor), and the figure of merit was good. In other words, the resistivity against Bs was higher and better than that of the conventional nanogranular magnetic film formed without rotation.
[0091] In Comparative Examples 5 and 6, in which other production conditions were changed, MX-rich was smaller than MX-poor, and the figure of merit was less than 1.20.
[0092] In Comparative Example 7, in which no pretreatment was performed, the film peeled off from the substrate and could not be evaluated.
[0093] (Experimental Example 2) Comparative Examples 8 to 10 and Examples 5 to 8 were carried out under the same conditions as Example 2, except that the rotation speed was changed from 1 rpm to 40 rpm. Similarly, Comparative Examples 11 to 12 and Examples 9 to 11 were carried out under the same conditions as Example 3, except that the rotation speed was changed from 2 rpm to 40 rpm. Comparative Examples 13 to 14 and Examples 12 to 14 were carried out under the same conditions as Example 4, except that the rotation speed was changed from 2 rpm to 40 rpm. The results are shown in Table 2.
[0094] [Table 2]
[0095] As can be seen from Table 2, Examples 5 to 14, in which MX-rich was greater than MX-poor, had good performance indices, similar to Examples 2 to 4. On the other hand, Comparative Examples 8 to 14, in which MX-rich was less than MX-poor, did not all have good performance indices.
[0096] (Experimental Example 3) Comparative Examples 15 to 26 and Examples 15 to 26 shown in Table 3 were carried out under the same conditions as Comparative Examples 2 to 4 and Examples 2 to 4, except that additive element chips made of additive elements were placed on the sputtering target. The shape of each additive element chip was a rectangular parallelepiped with the two largest sides being a 5 mm square and the thickness being about 0.5 mm. The number of additive element chips was set so that the compositions of the first phase and the second phase of the nanogranular magnetic film finally obtained were the compositions shown in each table, and V1 / (V1+V2) was close to the value of Example 1. The composition of each phase of the nanogranular magnetic film shown in each table was set to a composition on the assumption that all of the additive elements were contained in the first phase. It was actually confirmed that the additive elements were substantially all contained in the first phase in Experimental Examples 3 to 4 and 6 to 8.
[0097] First, the formula of the performance curve was derived from the comparative examples in which the type and amount of added elements were the same and only the ratio of Fe to Co was different. The formula of the performance curve derived from the comparative examples 15 to 17 in which 1 atomic % of Nb was added was y = 0.0033 × x -11.11 The performance curve equation derived from Comparative Examples 18 to 20, in which 2 atomic % Nb was added, is y = 0.0020 × x -11.18 The performance curve equation derived from Comparative Examples 21 to 23, in which 5 atomic % Nb was added, is y = 0.0008 × x -11.16 The performance curve equation derived from Comparative Examples 24 to 26, in which 10 atomic % Nb was added, is y = 0.0004 × x -11.3 It was.
[0098] The performance curve equation derived from Comparative Examples 27 to 29, in which 2 atomic % Mo was added, is y = 0.0016 × x -11.37 Performance derived from Comparative Examples 30 to 32 in which 2 atomic % Cu was added The equation of the curve is y=0.0022×x -11.05 It was.
[0099] The resistivity obtained by substituting the Bs value of each nanogranular magnetic film into the formula of the performance curve derived from a comparative example in which the type and amount of added element were the same was used as the reference resistivity.Then, the value obtained by dividing the measured resistivity of each nanogranular magnetic film by the reference resistivity was used as the performance index.The results are shown in Tables 3 and 4.
[0100] [Table 3]
[0101] [Table 4]
[0102] As can be seen from Tables 3 and 4, in all of the examples in Tables 3 and 4 in which the rotating plate was rotated at a rotation speed of 12 rpm, MX-rich was greater than MX-poor, and the performance index was good.
[0103] (Experimental Example 4) In Experimental Examples 1 to 3, three comparative examples were prepared according to the type and amount of added element, and the formula of the performance curve was derived. In Experimental Example 4, a method for provisionally confirming the characteristics of the nanogranular magnetic film by a simple method was examined.
[0104] The performance curve equation is derived by power approximation. Therefore, the general equation is y=A×x B It is expressed as:
[0105] Comparing the performance curves derived in Experimental Examples 1 to 3, the change in the value of A due to the change in the content of the additive element is large, but the change in the value of B is small. On the other hand, if the content of the additive element is the same, even if the type of additive element is changed, the change in the value of A and the value of B are small.
[0106] Therefore, even if the type of additive element is different, it is considered possible to perform a sufficiently accurate evaluation by calculating the figure of merit assuming that the type of additive element is Nb.
[0107] The A and B of the performance curves derived from Comparative Examples 2 to 4 and 15 to 26 are A = 0.0044, B = -11.25 when there is no added element (0% added element), A = 0.0033, B = -11.11 when there is 1% added element, A = 0.0020, B = -11.18 when there is 2% added element, A = 0.0008, B = -11.16 when there is 5% added element, and A = 0.0004, B = -11.30 when there is 10% added element. Therefore, the value of A needs to be selected according to the concentration of the added element, and a fixed value can be used for B regardless of the concentration of the added element.
[0108] The method of selecting A or B in the method of provisionally confirming the characteristics of the nano-granular magnetic film using a simple method will be described below in detail.
[0109] (How to select A) Create a graph with the amount of added element (%) on the horizontal axis and the value of A on the vertical axis. Then, plot points a (0,0.0044), b (1,0.0033), c (2,0.0020), d (5,0.0008), and e (10,0.0004) on the graph. Furthermore, connect points a and b with a line, connect points b and c with a line, connect points c and d with a line, and connect points d and e with a line. Use the resulting line graph to select A according to the amount of added element.
[0110] For example, when the amount of the added element is 0.6%, the selected A is 0.0044×0.4+0.0033×0.6=0.00374.
[0111] (How to select B) Regardless of the concentration of the added element, -11.20 is selected as B. This value of B is the arithmetic mean of -11.25, -11.11, -11.18, -11.16, and -11.30, which are the values of B for each of the above-mentioned amounts of added element.
[0112] (Definition of Simplified Performance Indices) General formula y=A×x BThe formula obtained by substituting A and B selected using the above selection method according to the amount of additive was defined as the simplified performance curve formula, the standard resistivity calculated from this formula as the simplified standard resistivity, and the performance index calculated from the simplified standard resistivity and the actual measured resistivity value as the simplified performance index. By using the simplified performance curve formula, it is possible to calculate the simplified performance index and evaluate the characteristics without producing a sample with a rotation speed of 0 rpm.
[0113] The performance index and the simplified performance index were compared for Comparative Examples 11-12 and Examples 3, 9-11, which were essentially the same except for the change in rotation speed. Since these samples contained 0% added elements, the parameters of the simplified performance curve equation were A = 0.0044 and B = -11.20. The calculation results of the simplified performance index are shown in Table 5 together with the performance index.
[0114] The performance index and simplified performance index were compared for Examples 18-20, 27-29, and 30-32, which have different types of additive elements with an additive amount of 2%. Since the additive amount is 2%, the parameters of the simplified performance curve equation are A = 0.0020 and B = -11.20. The calculation results of the simplified performance index are shown in Table 6 together with the performance index.
[0115] [Table 5]
[0116] [Table 6]
[0117] In all the comparative examples and examples shown in Tables 5 and 6, the performance index and the simplified performance index are not identical but are relatively close to each other. Therefore, the simplified performance index allows for a sufficiently accurate evaluation.
[0118] (Experimental Example 5) Examples 33 to 44 were carried out under the same conditions except that the type of additive element was changed from Examples 19, 28, and 31, Examples 45 to 46 were carried out under the same conditions except that the type of additive element was changed from Example 22, and Examples 47 to 48 were carried out under the same conditions except that the type of additive element was changed from Example 25 to determine MX-rich, MX-poor, and simplified performance index. The results are shown in Table 7.
[0119] [Table 7]
[0120] From Table 7, even if the type of additive element is changed, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified figure of merit is good. Even if three comparative examples are made for each composition of the embodiment and the figure of merit is calculated, the calculated figure of merit is likely to be 1.20 or more.
[0121] (Experimental Example 6) Changes in MX-rich, MX-poor, and simplified performance index when the rotation speed was changed during the manufacture of nanogranular magnetic films to which additive elements were added were confirmed. Comparative Examples 33-34 and Examples 49-50 were carried out under the same conditions as Example 31, except that the rotation speed was changed. Comparative Examples 35-36 and Examples 51-52 were carried out under the same conditions as Example 39, except that the rotation speed was changed. Comparative Examples 37-38 and Examples 53-54 were carried out under the same conditions as Example 44, except that the rotation speed was changed. The results are shown in Table 8.
[0122] [Table 8]
[0123] From Table 8, in Examples 31, 39, 44, and 49 to 54, MX-rich was greater than MX-poor, and the simplified performance index was good. In other words, no difference due to the type of added element could be confirmed.
[0124] (Experimental Example 7) The experiment was carried out under the same conditions as in Example 3, except that the second phase compound was changed from SiO2. In Examples 62 to 64, the ratio of SiO2 to Al2O3 in the second phase was changed. In addition, in Experimental Example 7, even when the type of compound contained in the second phase was different, the compound was considered to be equivalent to SiO2 and a simplified performance index was calculated. The results are shown in Table 9.
[0125] [Table 9]
[0126] From Table 9, even if the second phase compound is changed, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified performance index is also good. Even if three comparative examples are made for each example composition and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.
[0127] (Experimental Example 8-1) The experiment was carried out under the same conditions as in Example 3, except that V1 / (V1+V2) was changed significantly. In addition, in Experimental Example 8-1, even when V1 / (V1+V2) was significantly different, the simplified performance index was calculated assuming that V1 / (V1+V2) was about 46%. The results are shown in Table 10-1.
[0128] [Table 10-1]
[0129] From Table 10-1, even if V1 / (V1+V2) is changed significantly, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified performance index is also good. Even if three comparative examples are made for each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.
[0130] (Experimental Example 8-2) The ratio of Fe to Co in the first phase was varied for Examples 66, 67, 102, and 103. The results are shown in Table 10-2.
[0131] Furthermore, the compounds contained in the second phase were varied in Examples 103 and 108 to 110. The results are shown in Table 10-2.
[0132] [Table 10-2]
[0133] From Table 10-2, even if the composition of the first phase and / or the compound contained in the second phase are changed, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified performance index is also good. Even if three comparative examples are produced for V1 / (V1+V2) of each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.
[0134] (Experimental Example 8-3) Examples 67, 102, 103, 108-110, and 117-120 were carried out in the same manner, except that nitrogen was introduced into the second phase. In order to introduce nitrogen into the second phase, nitrogen was introduced into the process gas during sputtering together with 0.2% oxygen. The ratio of nitrogen to the total amount of oxygen and nitrogen in the second phase (N / (N+O)) was changed by changing the nitrogen concentration in the process gas. The results are shown in Table 10-3.
[0135] In Examples 121 to 124, Ar gas with 1% nitrogen was used as the process gas. In Examples 125 to 128, Ar gas with 2% nitrogen was used as the process gas. In Examples 129 to 132 and 139 to 142, Ar gas with 4% nitrogen was used as the process gas. In Examples 133 to 136, Ar gas with 6% nitrogen was used as the process gas. In all Examples, the flow rate of the process gas was set to 20 sccm in total for Ar and nitrogen.
[0136] The method for measuring N / (N+O) is explained below. When sputtering the nanogranular magnetic film, a silicon substrate with a thermal oxide film and Ni foil measuring 20mm x 20mm x 50μm were prepared. The length in the thickness direction was 50μm. Then, the N / (N+O) ratio was measured for the nanogranular magnetic film formed on the Ni foil using the impulse heating melting extraction method with a LECO TC600.
[0137] [Table 10-3]
[0138] From Table 10-3, even if the composition of the first phase and / or the compound contained in the second phase are changed, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified figure of merit is also good. Even if three comparative examples are made for each example and the figure of merit is calculated, the calculated figure of merit is likely to be 1.20 or more.
[0139] (Experimental Example 8-4) Examples 143 to 158 were carried out in the same manner as Examples 121 to 124, except that an additive element chip made of an additive element was placed on the sputtering target as in Experimental Example 3. Furthermore, Examples 159 to 162 were carried out in the same manner as Examples 155 to 158, except that the nitrogen concentration of the process gas was changed to 6%. The results are shown in Table 10-4.
[0140] [Table 10-4]
[0141] From Table 10-4, even if the composition of the first phase and / or the compound contained in the second phase are changed, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified figure of merit is good. Even if three comparative examples are made for each example and the figure of merit is calculated, the calculated figure of merit is likely to be 1.20 or more.
[0142] (Experimental Example 8-5) For Examples 155 to 158, the ratio of Fe and Co in the first phase was changed to perform Examples 163 to 170. For Examples 155 to 158, the number of additive element chips was changed to perform Examples 171 to 174. Furthermore, for Example 156, the type of additive element was changed to perform Examples 175 to 184. The results are shown in Table 10-5.
[0143] [Table 10-5]
[0144] From Table 10-5, even if the composition of the first phase is changed, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified figure of merit is good. Even if three comparative examples are made for each embodiment and the figure of merit is calculated, the calculated figure of merit is likely to be 1.20 or more.
[0145] (Experimental Example 9) The experiments were carried out under the same conditions as in Examples 3, 103, and 134, except that the film thickness was changed significantly. In addition, in Experimental Example 9, even when the film thickness was significantly different, the simplified performance index was calculated assuming that the film thickness was about 5000 nm. The results are shown in Table 11.
[0146] [Table 11]
[0147] From Table 11, even if the film thickness is changed significantly, the MX-rich of the obtained nanogranular magnetic film is larger than the MX-poor, and the simplified performance index is good. Even if three comparative examples are made for each film thickness of the embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.
[0148] From the above examples, it is easier to absolutely increase both Bs and resistivity as the amount of additive element is smaller. From the viewpoint of absolutely increasing both Bs and resistivity, the formula of the performance curve derived from Comparative Examples 2 to 4 that do not contain additive elements, y=0.0044×x -11.25 It is more preferable that the figure of merit calculated using the following formula is 1.20 or more. [Explanation of symbols]
[0149] 1...Nanogranular magnetic film 11…Phase 1 12...Phase 2 111...Rotating member 111a...Rotating plate 111b...Rotation axis 113...Substrate 121...Sputtering equipment 123…Sputter target 131...Shutter
Claims
1. A nano-granular magnetic film having a structure in which minute domains of a first phase are dispersed in a second phase, the first phase includes Fe and Co, and the second phase includes a second phase compound that is one or more compounds selected from an oxide, a nitride, and a fluoride; A measurement range is set in the nanogranular magnetic film, the measurement range is divided into 80,000 or more 1 nm x 1 nm x 1 nm grids, Fe / (Fe + Co) of each grid and the second phase compound are measured in terms of atomic ratio, and each grid is classified into an MX-rich grid in which the concentration of the second phase compound is equal to or greater than the average concentration of the second phase compound, and an MX-poor grid in which the concentration of the second phase compound is less than the average concentration of the second phase compound, A nanogranular magnetic film in which the CV value of Fe / (Fe+Co) calculated for each MX-rich grid is larger than the CV value of Fe / (Fe+Co) calculated for each MX-poor grid.
2. 2. The nanogranular magnetic film according to claim 1, wherein a volume ratio of the first phase to a total volume of the first phase and the second phase is 40% or more and 65% or less.
3. 3. The nanogranular magnetic film according to claim 1, wherein an average value of Fe / (Fe+Co) calculated for each of the grids is 0.15 or more and 0.85 or less.
4. 3. An electronic component comprising the nanogranular magnetic film according to claim 1.
Citation Information
Patent Citations
Amorphous alloy containing nitrogen
JP1985152651A
Soft magnetic alloy and magnetic component
WO2023127199A1